2014
DOI: 10.1080/10298436.2014.893331
|View full text |Cite
|
Sign up to set email alerts
|

Review of very high-content reclaimed asphalt use in plant-produced pavements: state of the art

Abstract: Asphalt is the most recycled material in the USA at a re-use rate of 99%. However, by average only 10 -20% reclaimed asphalt pavement (RAP) is used in a given mix design and large part of the RAP is degraded for use in lower value applications. The amount of RAP in asphalt mixtures can be significantly increased with the application of good RAP management practice, readily available modern production technologies and advanced knowledge of mix design. This paper summarises the state-of-the-art approaches for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
121
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 312 publications
(127 citation statements)
references
References 32 publications
0
121
0
6
Order By: Relevance
“…Further research is also necessary to investigate the effect of rejuvenator dose optimization on the mixture performance-related properties. The effects of adding virgin binder and aggregates are likely to impose new challenges, including rejuvenator diffusion into the RAP binder as well as rejuvenator effect on blending of RAP and virgin binder [31,32,3]. Some of these questions are answered in other stages of this research and summarized in short video: http://youtu.be/y-rYvdGiEbY…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further research is also necessary to investigate the effect of rejuvenator dose optimization on the mixture performance-related properties. The effects of adding virgin binder and aggregates are likely to impose new challenges, including rejuvenator diffusion into the RAP binder as well as rejuvenator effect on blending of RAP and virgin binder [31,32,3]. Some of these questions are answered in other stages of this research and summarized in short video: http://youtu.be/y-rYvdGiEbY…”
Section: Discussionmentioning
confidence: 97%
“…One of the main limitations to allow higher RAP recycling is the aged RAP binder. Unless treated, it stiffens the mixture and can cause cracking failures of the pavement [3]. At low RAP content, softer virgin binder can be used to compensate for the aging effect.…”
Section: Introductionmentioning
confidence: 99%
“…One major advantage of production using WMA technologies is the potential to increase the Reclaimed Asphalt Pavement (RAP) and Reclaimed Asphalt Shingles (RAS) content in mixture (Bonaquist 2011a;Zaumanis and Mallick 2013;Kristjansdottir 2007). Since mixture workability is increased even at reduced temperature, less superheating is required for virgin aggregates when adding RAP and RAS.…”
Section: Productionmentioning
confidence: 99%
“…Zaumanis and Mallick [29] reviewed the state-of-the-art approaches for increasing the amount of RAP in asphalt mixtures above 40% and concluded that RAP content can be significantly increased with the application of good RAP management practices, readily available modern production technologies and advanced knowledge of mix design. Case studies from Germany, Netherlands, and South Africa have reported up to 50% RAP content in mixes [12] [21].…”
Section: Potential For Increased Rap In Wmamentioning
confidence: 99%
“…Environmental benefits include reduced emissions and fuel usage associated with extraction and transportation of virgin materials, reduced demands on non-renewable resources, and reduced landfill space for disposal of construction debris [28]. As it were, pushing for mixes having 100% RAP content could create a cycle of reuse that optimizes the utilization of natural resources and makes pavement construction a sustainable process [29]. What is more, the process of reclaiming and processing RAP materials has a very low environmental impact [8].…”
Section: Potential For Increased Rap In Wmamentioning
confidence: 99%